Clinical Profile of Male Patients Presenting with Breast Cancer in Kashmir Valley - Ulfat Ara Wani; Umeek Jeelani; Basharat Ara Wani; Shahida Nasreen (Indian Journal of Medical and Paediatric Oncology)
Introduction Breast cancer is a rare disease in males with unknown etiology and variable rate of incidence among different ethnic and geographical groups.